The nexus between maternal antenatal care attendance, newborn postnatal care and neonatal mortality in India: a matched case-control study - Wahengbam Bigyananda Meitei; Abhishek Singh (BMC, 2024)
Abstract Introduction Our study examines the relationship between newborn postnatal care and neonatal mortality stratified by maternal antenatal care attendance under a matched case-control framework. Methods Data from the fifth round of the National Family Health Survey was used. A total of 172,079 recent births to eligible women (15-49 years) in five years preceding the survey were included in the study. We used the conditional logistic regression model, a commonly used regression model to fit matched case-control data to examine the effects of newborn postnatal care on neonatal mortality. The mother's age at birth of the newborn, previous birth intervals, birth order of the newborn, and birthsize of the newborn were included as the matching variables. Results Newborns receiving postnatal care within two days or more than two days of birth are less likely to die during the neonatal period. Preferences for newborn postnatal care were also observed to increase with more maternal antenatal care visits. Our study also found a lower risk of neonatal mortality among those newborns whose umbilical cord was examined within two days of birth, regardless of the number of maternal antenatal care visits. Similarly, the risk of newborn deaths was lower among babies whose body temperature was measured within two days of birth. The tendency to breastfeed their newborns within an hour after delivery was considerably higher among those births that occurred to mothers who had a higher number of maternal antenatal care visits. The risk of newborn deaths was also observed to be lower among those born in public or private healthcare facilities. Conclusion Considering the cohesive nature of the relationship between neonatal mortality and maternal and child healthcare utilisation, strategic planning and management of the existing policies and programmes related to accessibility, availability, and affordability of maternal and child healthcare services is needed to achieve goal 3.2 of the Sustainable Development Goals. Promoting cost-effective measures such as continuous monitoring of the baby's body temperature and umbilical cord care could also effectively help reduce neonatal mortality.